Fibromyalgia Syndrome and Vitiligo: A Novel Association - Oula S. KHUDHAIR; Faiq I. GORIAL; Ammar F. HAMEED (Archives of Rheumatology, 2018)
Objectives: This study aims to assess the relationship between fibromyalgia syndrome (FMS) and vitiligo in Iraqi patients and evaluate the predictors of this relationship, if present. Patients and methods: The case-control study included 100 Iraqi patients (46 males, 54 females; mean age 30.4±14 years; range 15 to 65 years) with vitiligo and 200 age- and sex-matched healthy controls (74 males, 126 females; mean age 30.3±9.4 years; range 15 to 62 years). Baseline characteristics of patients and controls were recorded. The 2012 Canadian Guidelines criteria were used for the diagnosis of FMS and applied to all patients and controls. Results: Prevalence of FMS in vitiligo patients and controls was 12% and 7%, respectively (p=0.15, odds ratio=1.8, 95% confidence interval=0.8-4.08). FMS symptoms in vitiligo patients were fatigue (46%), diffuse body pain (34%), sleep disturbance (33%), cognitive dysfunction (30%), and mood disorders (23%), while visceral involvements were central nervous system (52%), skin (35%), gastrointestinal tract (32%), cardiovascular system- respiratory system (16%), genitourinary tract (8%), and ear nose throat (7%). Of vitiligo patients, FMS was significantly more common among females (22.2%) compared to none among males (0%) (p<0.05). Prevalence of FMS was restricted to female sex only and a significantly higher prevalence rate of FMS was found among female vitiligo patients (22.2%) compared to controls (9.5%). Receiving phototherapy significantly increased the risk of having FMS by 5 times compared to female patients not receiving phototherapy. Use of any steroid reduced the risk of having FMS by 2.5 times (inverse of odds ratio=0.4) among females patients (p>0/05). No significant association was found between FMS in vitiligo patients and age, disease duration, type of vitiligo, use of any immunosuppressant and body mass index (p>0.05). Conclusion: Fibromyalgia syndrome was more prevalent in vitiligo patients compared to controls, which was clinically important but statistically not significant. There was a significant association between FMS in vitiligo patients and female sex, severe form of vitiligo, and receiving phototherapy. This may suggest that early diagnosis of FMS in vitiligo patients may help in early treatment and subsequently improve patients’ quality of life.